ABS ANALISIS NILAI TUKAR RUPIAH DAN INFLASI TERHADAP RETURN SAHAM INDUSTRI PERBANKAN - Agus Budi Santosa; Sri Nawatmi (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
The role of the banking industry is an important sector in driving economic growth. Tight competition in the banking industry requires bank management to improve its performance. Financial reports are a means for investors to find out financial condition and make investment decisions. Investors monitor the performance of banking companies in terms of profit objectives from stock returns. This research will analyze the influence of external factors through the Rupiah exchange rate and inflation variables on stock prices. The tool of analysis in uses multiple linear regression to determine the influence between the independent variable and the dependent variable. The research data uses data for the 2018 - 2020 period. Finding on the research results, it is concluded that inflation has no effect on stock returns, while exchange rate has a negative effect to stock prices.